INTEGRATION OF EARLY CHILDHOOD THEMATIC LEARNING MODELS BASED ON ISLAMIC EDUCATION IN NURUL FATAH KINDERGARTEN KALIBARU BANYUWANGI - Siti Nofita Widayatul Hasanah BZ; Luluk Mukaromah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This research is based on early childhood education, conducted from birth to age 6 years which is adjusted to the level of child development. Therefore, early childhood education is developed creatively through the development of a curriculum based on Islamic Religious Education in a thematic learning model that has been carried out by Nurul Fatah Kalibaru Banyuwangi Kindergarten. Religious Education-based curriculum is learning whose learning process uses an Islamic teaching approach. In this study, the author used qualitative research methods. Namely research to describe an event, symptom, and event that occurs at the moment. The results of the research are 1) In every learning process using the national curriculum which is integrated with Islamic Religious Education. So children have been introduced to the teachings of Islam from an early age. Because Islamic education is considered good because it is in accordance with the nature of children in providing education. 2) Thematic Learning at Nurul Fatah Kalibaru Banyuwangi Kindergarten using the National curriculum with a thematic approach. Thematic learning at Nurul Fatah Banyuwangi Kindergarten is used to link Islamic education learning with daily learning. Thematic learning is carried out in groups that will change themes every week. For example, with the theme of the self, the child can know the parts of his body so that he can know His creator and be grateful to the creation of Allah SWT.